Euxanthone Impairs the Metastatic Potential of Osteosarcoma by Reducing COX‐2 Expression. Issue 8 (21st December 2018) - Chen, Xiaodong; Deng, Min; Zhou, Xinshe; Wang, Xuyi; Ye, Yuchen; Zhu, Jun; Jiang, Huafeng; Chen, Xiaotian; Zha, Wenju
ABSTRACT: Osteosarcoma (OS) is one of the most common malignancies of bone. This study was aimed to explore the anti‐metastatic effect of euxanthone on OS. Adhesion assay and Transwell assay were used to examine the effect of euxanthone on adhesion, migration and invasion of OS cells. COX‐2‐over‐expressing plasmid was applied to transfect OS cells to assess whether COX‐2 affects the anti‐metastatic function of euxanthone. PDCD4 knockdown and miR‐21 mimic were applied to assess whether euxanthone suppresses the transactivation of c‐jun via modulating miR‐21‐PDCD4 signaling. The effect of euxanthone in vivo was also examined by lung metastasis assay. Euxanthone, a xanthone derivative extracted from Polygala caudata, has been found to exhibit anti‐neoplastic activities. In present study, our results showed that euxanthone suppressed cell adhesion, migration, and invasion in OS cells. Our experimental data also showed that repression of COX‐2 by euxanthone mediated its anti‐metastatic activities. Moreover, our findings revealed that euxanthone modulated the COX‐2 expression through the miR‐21/PDCD4/c‐jun signaling pathway. The anti‐metastatic activities of euxanthone were also validated in a pulmonary metastasis model. Taken together, our results highlighted the potential of euxanthone to be used in the treatment of OS. Anat Rec, 302:1399–1408, 2019. © 2018 Wiley Periodicals, Inc.